Children who engaged in interpersonal problematic sexual behaviors. (July 2020) - DeLago, Cynthia; Schroeder, Christine M.; Cooper, Beth; Deblinger, Esther; Dudek, Emily; Yu, Regina; Finkel, Martin A.
Abstract: Background: Over one-third of inappropriate sexual contact experienced by children is initiated by other children. Many studies examined child initiators (CIs) of interpersonal problematic sexual behaviors (IPSBs). This study uniquely links CI information with types of sexual contact as described by children they engaged in IPSBs. Objective: Describe CIs' characteristics and types of sexual acts they initiated. Participants/Setting: Medical charts of CIs and children they engaged in IPSBs. Examinations occurred between 2002 and 2013. Methods: Retrospective chart review. Results: Most CIs were male (83%) and related to the child they engaged in IPSBs (75%); mean age was 10 years (range 4–17); 58% reported viewing sexually explicit media; 47% experienced sexual abuse. Most CIs (68%) engaged in multiple types of IPSBs. Children who experienced IPSBs initiated by males reported engagement in greater numbers of invasive acts (t(216) = 2.03, p  = .043). Older CIs were more likely than younger CIs to report viewing sexually explicit media (χ 2 (1) = 7.81, p  = .007) and those who did were more likely to initiate more invasive acts (t(169) = 2.52, p  = .013) compared to CIs who did not. Conclusions: In this study, most CIs were young and experienced multiple adverse events; the most common types of IPSBs were invasive; and over half the CIs had been exposed to sexually explicit media, which was associated with initiating invasive sexual acts. These findings suggest aiming prevention efforts at young children to help them manage exposure to sexually explicit media and redress victimization experiences.